PARTISIPASI MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KELURAHAN PADANG BULAN SELAYANG I KECAMATAN MEDAN SELAYANG KOTA MEDAN - Sarido Emelius Sagala; Elita Dewi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Land tax and rural and urban buildings should be potential enough to affect the increase in Medan City. However, the problem that occurs is that there are still people as taxpayers who do not pay because of the lack of awareness from the taxpayer community to pay taxes. People still think that officials often abuse taxes, people see no benefit because there are still many damaged roads. The purpose of the research in this study is to find out and analyze the participation of the community in paying land and building taxes in the Padang Bulan Selayang I Village, Medan Selayang District, Medan City. The research method used is descriptive with a qualitative approach. Data collection was carried out through interviews, observation and documentation. The data obtained were then analyzed qualitatively using the Oakleys Participation Theory. The results showed that the participation of the people of Outahan Padang Bulan Selayang I in paying Land and Building Tax can be seen from a good level of awareness in fulfilling their rights and obligations as citizens and the level of trust in the government. There is a contribution made by the community with the participation of the community in paying Land and Building Tax. The government organizes by socializing to the community that it is important to pay Land and Building Tax. The responsibility of the community is to obediently pay the Land and Building Tax and be timely in paying the Land and Building Tax.